An Alternating Direction Method for Mixed Gaussian Plus Impulse Noise Removal - Si Wang; Ting-Zhu Huang; Xi-le Zhao; Jun Liu (Abstract and Applied Analysis)
A combined total variation and high-order total variation model is proposed to restore blurred images corrupted by impulse noise or mixed Gaussian plus impulse noise. We attack the proposed scheme with an alternating direction method of multipliers (ADMM). Numerical experiments demonstrate the efficiency of the proposed method and the performance of the proposed method is competitive with the existing state-of-the-art methods.